2018
DOI: 10.1063/1.5046686
|View full text |Cite
|
Sign up to set email alerts
|

Highly-efficient thermoelectric pn-junction device based on bismuth telluride (Bi2Te3) and molybdenum disulfide (MoS2) thin films fabricated by RF magnetron sputtering technique

Abstract: Layered structure bismuth telluride and molybdenum disulfide thin films were successfully deposited on different substrates using radio-frequency magnetron sputtering technique. The structural, morphological, and thermoelectric transport properties of bismuth telluride and molybdenum disulfide thin films have been investigated systematically to fabricate high-efficient thermal energy harvesting thermoelectric device. The magnitude of the Seebeck coefficient of bismuth telluride thin films decreases with increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The individual planar patterns devices were placed 0.15 cm apart. The size of our entire thermoelectric structure with multiple planar legs was 7.5 cm × 3.6 cm 35 . Both MoS 2 and WS 2 films are deposited at the substrate temperature of 450 °C and annealed at 600 °C in Argon environments for 1 hour.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The individual planar patterns devices were placed 0.15 cm apart. The size of our entire thermoelectric structure with multiple planar legs was 7.5 cm × 3.6 cm 35 . Both MoS 2 and WS 2 films are deposited at the substrate temperature of 450 °C and annealed at 600 °C in Argon environments for 1 hour.…”
Section: Methodsmentioning
confidence: 99%
“…All the films are grown for different period of time from 10-45 minutes to obtain various film thickness. The films were annealed at 600 °C and 700 °C under argon atmosphere at a flow rate of 50 sccm to improve the crystallinity of the films 35 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inspired by the success of the metallurgical junctions in transforming Silicon into many sophisticated semiconductor devices, they were attempted in transforming thermoelectric materials into cost-effective devices. By directly connecting the nand the p-type thermocouple's legs [16][17][18][19][20][21][22][23][24][25][26] , it was found that so formed p-n junction enhanced the device's lifetime and efficiency. Although the effect of such a p-n junction on the Seebeck coefficient is modest, it was proved to be effective in enhancing the device durability 27,28 .…”
Section: Introductionmentioning
confidence: 99%